Combined effect of plastic litter and increased atmospheric nitrogen deposition on vegetative propagules of dune plants: A further threat to coastal ecosystems. (November 2020) - Menicagli, Virginia; Balestri, Elena; Vallerini, Flavia; Castelli, Alberto; Lardicci, Claudio
Abstract: Large amounts of non-biodegradable plastics are currently deposited on beach-dune systems, and biodegradable plastics could enter these already declining habitats in coming years. Yet, the impacts of plastics on vegetative recruitment, a plant strategy playing a key role in dune stabilization, are unknown. Whether these pollutants interact with increased atmospheric nitrogen (N) deposition, a major global driver of plant biodiversity loss, in affecting plant communities of such nutrient-poor habitats, and how plant-plant interactions mediate their effects need to be explored. In a one-year field experiments, we examined individual and combined effects of plastic (non-biodegradable, biodegradable), N deposition (ambient, elevated) and biotic condition (no interaction, interaction with a conspecific or with a hetero-specific) on the colonization success and growth of vegetative propagules of dune plants. Thinopyrum junceum and Sporobolus pumilus were chosen as models because they co-occur along Mediterranean dunes and differ in ecological role (dune- vs . non dune-building) and photosynthetic pathway (C3 vs . C4). For both species, survival probability was reduced by non-biodegradable plastic and elevated N by up to 100%. Thinopyrum junceum survival was also reduced by S. pumilus presence. Elevated N and biodegradable plastic reduced T. junceum shoot biomass when grown alone and with a conspecific, respectively; these factors in combination mitigated their negative individual effects on root biomass. Biodegradable plastic increased S. pumilus shoot and root biomass, and in combination with elevated N caused a greater biomass investment in belowground (root plus rhizome) than aboveground organs. Non-biodegradable plastic may be a further threat to dune habitats by reducing plant colonization. Biodegradable plastic and increased N deposition could favour the generalist S. pumilus and hinder the dune-building T. junceum . These findings highlight the urgency of implementing measures for preventing plastic deposition on beaches and reducing N input. Graphical abstract: Image 1 Highlights: Plastic litter and increased nitrogen (N) input are global environmental problems. Combined effect of plastic, high N and biotic condition on dune plants is unknown. Non-biodegradable plastics reduce T. junceum and S. pumilus survival. Biodegradable plastics and increased N promote S. pumilus growth. Plastics and increased N in combination could further threat dune ecosystems. Abstract : Non-biodegradable plastic litter strongly reduced the colonization of coastal dunes by plants and biodegradable plastic in combination with increased nitrogen deposition favoured the generalist S. pumilus over the typical dune-building T. junceum by differentially affecting their growth.